Pelatihan Penguasaan Kosa Kata Bahasa Asing Di Komunitas Griya Studi Boyolali - Anni Nurul Hidayati; Achmad Mufid Marzuqi (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2024)
This program is implemented to assist the Griya Studi Course to improve the English language skills of early childhood children. This program also aims to foster student interest in learning English. It is hoped that after this program the children's English vocabulary mastery skills will increase. The technique used in this training program is Fun English Learning through songs. Students are expected to be active and interested in participating in the English learning process. With a variety of material variations that will be given, it is hoped that students will not feel bored. The output and the targets that will be achieved after this training program are the publication in journals with ISSN/proceedings and through online media. Second, it is expected that students have an interest in participating in learning and can master a variety of vocabularies.